2011
DOI: 10.1016/j.drugalcdep.2010.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Injury, pain, and prescription opioid use among former National Football League (NFL) players

Abstract: Background-Athletes with injury-related pain, especially National Football League (NFL) players, are at increased risk for opioid use and misuse which may result in medical, psychiatric and social problems. This is the first study to evaluate the intersection of sports pain and opioid use and misuse among former NFL players.Methods-A telephone survey of 644 retired NFL players from the 2009 Retired Players Association Directory was conducted (53.4% completion rate) from March to August 2010.Results-Over half (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(127 citation statements)
references
References 14 publications
4
123
0
Order By: Relevance
“…Interestingly, in a post-mortem study of 34 opiate abusers under the age of 40, multifocal NFTs were common, and 19% of the control subjects had NFTs in the entorhinal cortex (Ramage et al, 2005). Some retired professional athletes have a problem with opiate abuse (Cottler et al, 2011). In a second study, this research group also reported elevated levels of hyperphosphorylated tau in drug users, similar to that of elderly control subjects, but far less than is seen in AD (Anthony et al, 2010).…”
Section: Neuropathologymentioning
confidence: 92%
See 1 more Smart Citation
“…Interestingly, in a post-mortem study of 34 opiate abusers under the age of 40, multifocal NFTs were common, and 19% of the control subjects had NFTs in the entorhinal cortex (Ramage et al, 2005). Some retired professional athletes have a problem with opiate abuse (Cottler et al, 2011). In a second study, this research group also reported elevated levels of hyperphosphorylated tau in drug users, similar to that of elderly control subjects, but far less than is seen in AD (Anthony et al, 2010).…”
Section: Neuropathologymentioning
confidence: 92%
“…In two recent reviews of the literature, it was concluded that there is insufficient scientific evidence to conclude that CTE is a risk factor for suicide (Iverson, 2014;Wortzel et al, 2013). That said, former NFL players might be at increased risk for depression (Gonzalez et al, 2010;Schwenk et al, 2007), and their rate of chronic pain and opioid use is high (Cottler et al, 2011).…”
Section: Depressionmentioning
confidence: 99%
“…1,2 In a review of over 2500 retired players, 74% reported suffering a muscle or tendon injury in their career and approximately half reported at least 1 knee injury. 3 Long-term consequences of injury include general musculoskeletal disability, increased risk for opioid misuse, 4 and a threefold risk for knee arthritis. 3 Researchers have prospectively identified risk factors for injury in high school and college levels of competition in football.…”
mentioning
confidence: 99%
“…Since 2009, center Randy Grimes, tight end Dan Johnson, guard Bob Newton, and offensive tackle Kyle Turley have all come forward to discuss their dependence on opioids in an attempt to lobby the league for better prevention, protection, and treatment for players with painkiller dependencies. Most notably, these lesser-known players all appeared as interviewees in ESPN's Outside the Lines program (Cottler et al, 2011), describing how pills are and were readily dispensed by team doctors "no questions asked." Moreover, a Drug Enforcement Agency spokesperson featured in the episode claimed that it is common for NFL team doctors to acquire and store large quantities of painkillers with no patient in mind.…”
Section: Racial Materialsizations: Nfl Policy Media Panic and The Wamentioning
confidence: 99%
“…1 Although the doped up athlete (usually a football player) returning heroically to the field of play is something of a clichĂ© in sports films and in the mythology of legendary former players such as Walter Payton, such images have served to naturalize painkiller use at the same time that they have failed to penetrate everyday mass media discourse about sport-at least until recently. One catalyst for current interest in painkiller use in sport was a 2011 episode of ESPN's "Outside the Lines," highlighting the results from a Washington University survey of 644 former National Football League (NFL) players, 52% of whom acknowledged using these drugs during their careers (Cottler et al, 2011). Of those players, 71% claimed to have misused such substances (by, for example, taking more pills than prescribed) and 63% said they obtained them from illegal sources such as teammates, coaches, trainers, and drug dealers.…”
Section: Introductionmentioning
confidence: 99%